The legacy of Fred Sanger - 100 years on from 1918 - Brownlee, G (Elsevier, 2018)
August 2018 marks the centenary of the birth of Frederick (Fred) Sanger (1918–2013), one of the most influential scientists of the 20th century. Few scientists transform a discipline in their lifetime. Fred Sanger did this, not once but twice. By devising methods for sequencing, he revolutionized our understanding of both proteins and nucleic acids gaining the Nobel Prize inChemistry twice. He is the only scientist to have achieved this honor.